Veredas à gênese de si-mesmo : explicitações preliminares à constituição e desenvolvimento da ipseidade - Marques, Cristian (2022)
The thesis aims to argue that the most proper experience we have of ourselves, of a certain uniqueness of the personal experience of oneself, called ipseity, has its genesis in the interpellation from otherness, supported by the promise. However, I argue that it is necessary to effect a leap-of-self in this interpellation to promote the happening of the self. Such originary elements are described as ontological indications of constituents of the genesis of ipseity, although they do not exhaust the elements of a complete phenomenology of this genesis. I present some of the originaries elements, by formal indications, in the genesis and development of the phenomenon of ipseity in a preliminary task of searching for how the possibility of the existence of self occurs. Ipseity is presented from a phenomenological perspective as that which one is properly, as coming into presence in the play of anticipating and having been, as alluding to taking oneself into prominence and reference in the horizon of selfunderstanding with the world. By genesis is indicated the happening in which the beginnings of the self is constituted and comes to be what it is. Therefore, investigating the how of the genesis of self is about making explicit the origin of this happening that makes possible the coming-to-be of self. The path chosen to make this explanation is in the framework of the phenomenological movement, in which the self is not given in advance as a substance or permanent core to which predicates adhere, but is understood rather as a possibility of hermeneutically constituted existence of being-inthe-world. The theoretical starting point is the path opened by Martin Heidegger with his analysis of Dasein, repositioning the problem of the body-self and alterity to think about the genesis of self.